Instructional System of Research Education Program and Research Skills Productivity of Students in Science and Technology Oriented High Schools in Caraga Region - Jacob, Benjie P. (JPAIR Institutional Research, 2018)
The research subject is one of the effective tools to equip secondary students under Science and Technology Oriented High School (STOHS) curriculum with the appropriate research skills that will capacitate students to prepare research reports, investigatory projects and research proposal utilizing information obtained from the library and online resources. This mixed method study aimed to determine the significant difference in the ratings of the 278 respondents on the extent of optimal functioning of the instructional system of the research education program and in identifying the significant relationship between the instructional system and the research skills productivity of teachers and student-researchers in Caraga Region, Philippines. The study revealed that the instructional system was at a moderate level while the research skills productivity was at a nadir level. Also, it was divulged that there was a significant difference in the extent of the optimal functioning of the instructional system in teaching research education. Using FGD, the facilitating factors were good academic qualifications of the teacher-researchers, sufficient school facilities, the standard form of assessment, and the existence of the reward system while the hindering factors were the resource generation, absence of school's research journals and scholarships, and discouraging research environment. This paper suggested that schools should publish researches in journals, improve utilization of researches, look for potential sponsors and should tie up with external evaluators/organizations.
Keywords: Research Education Program; instructional system; research skills productivity; mixed method; Philippines